A Subgroup Analysis Found no Diminished Response to Buprenorphine Transdermal System Treatment for Chronic Low Back Pain Patients Classified with Depression. Issue 4 (11th April 2015) - Yarlas, Aaron; Miller, Kate; Wen, Warren; Lynch, Shau Yu; Munera, Catherine; Dain, Bradley; Pergolizzi, Joseph V.; Raffa, Robert; Ripa, Steven R.
Abstract: Background: Chronic pain (CP) patients with depression typically exhibit worse post‐treatment outcomes than nondepressed CP patients. The cause is often assumed to reflect a differential response to treatment, neglecting other potential explanations, such as the continuation of differences in pretreatment outcomes. This post hoc analysis examines whether worse post‐treatment outcomes for depressed patients with chronic low back pain (CLBP) are driven by reduced treatment efficacy. Methods: Data were from opioid‐naïve adult patients with moderate‐to‐severe CLBP who participated in a randomized, placebo‐controlled, double‐blind clinical trial of Butrans ® (buprenorphine) Transdermal System (BTDS) for pain relief. Depression screening was based on baseline SF‐36v2 Mental Health subscale scores. Patient‐reported measures of pain severity, pain interference, quality of life, sleep problems, and functional disability were administered at screening and during the study. Differential treatment efficacy for each outcome was examined using analysis of covariance models that included interaction terms between treatment arm and depression status. Results: At baseline, patients classified as depressed showed greater pain interference, lower quality of life, more sleep problems, and greater functional disability than nondepressed patients; the two groups did not differ in pain severity. No statistically significant interactions between treatment arm and depression status were observed. The direction of improvement post‐treatment favored the depressed group on nine of seventeen outcomes. Conclusions: Results do not support a differential response to BTDS treatment between depressed and nondepressed CLBP patients across a variety of patient‐reported outcomes. These findings raise the question of whether depressed mood actually moderates the effectiveness of treatment in CP patients.